1983
DOI: 10.1177/030089168306900111
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study with Adjuvant Hormone Therapy in Figo Stage I Endometrial Carcinoma with Myometrial Invasion

Abstract: A pilot study with adjuvant hormone therapy in FIGO stage I endometrial carcinoma with myometrial invasion was carried out. All patients received total abdominal hysterectomy and bilateral salpingo-oophorectomy plus complementary radium therapy on the vaginal stump. After the conventional treatment, patients were randomly allocated to adjuvant hormone therapy or no further treatment. Hormone therapy consisted of gestonorone caproate (17α-hydroxy-19-norpregn-4-en 3,20 dione caproate) administered i.m. at the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…In the nine trials identified, patients were randomized to either adjuvant progestogen therapy or to a control group with no adjuvant therapy [6][7][8][9][10][11][12][13][14] . In seven trials, patients in the control group received no further treatment [6][7][8][9][10][11][12] ; in two trials, patients in the control group received a placebo control.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the nine trials identified, patients were randomized to either adjuvant progestogen therapy or to a control group with no adjuvant therapy [6][7][8][9][10][11][12][13][14] . In seven trials, patients in the control group received no further treatment [6][7][8][9][10][11][12] ; in two trials, patients in the control group received a placebo control.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…In seven trials, patients in the control group received no further treatment [6][7][8][9][10][11][12] ; in two trials, patients in the control group received a placebo control. One trial also included a third group of patients randomized to receive tamoxifen 6 .…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations